Anti-Europeanism, populism and European integration in a historical perspective - Guiso, Andrea; Pasquinucci, Daniele (New York : Routledge, 2024)
"This book explores the long-term origins of populist Euroscepticism. Taking a historical perspective to move beyond explaining present-day expressions of opposition to the European Union in isolation, this book reveals the historical sedimentation of the several ways and forms taken over decades by opposition towards European integration. As such, this approach - with contributions from across disciplines - explains not just the past of Euroscepticism, but also its current nature and future prospects. This book will be of key interest to scholars and students of European History, European Politics and Studies and more broadly to Political Science, International Relations, the Humanities and Social Sciences"--
Part 1 . Historicizing Populist Euroscepticism. Distinct but converging: historicising populist Euroscepticism / Daniele Pasquinucci -- European integration and democratic legitimacy: a historical assessment of the institutional and economic roots of populist Euroscepticism / Andrea Guiso -- Euroscepticism from a historical viewpoint: the need for further definition and a brief periodisation / Antonio Varsori -- Part 2. The Historical Roots of Brexit. British nationalism and Brexit / Mark Gilbert -- Populism and Euroscepticism: The UK Labour Party since William King -- Brexit and Margaret Thatcher's Eurosceptic legacy / Domenico Maria Bruni and Laura Chiara Cecchi -- Part 3. France and Germany: The Old Couple in the Face of Populist Euroscepticism. The French Communist Party facing the European defense community (1950-1954): between propaganda, ideology and populism / Martial Libera -- From "Front" to "Rassemblement National": Radical Right Populist Euroscepticism in France / Nicola Genga -- Something new on the German front: The alternative für Deutschland and Europe / Federico Niglia -- Part 4. National Varieties of Populist Euroscepticism. The construction of a Dutch Eurosceptic tradition by contemporary populist political parties / Robin de Bruin -- Euroscepticism and Vox: Is it the end of Spanish exceptionalism? / Maria Elena Cavallaro and Giorgia Priorelli -- "Against the hegemony of Brussels": The Anti-Europeanism of right-wing political parties in Poland / Joanna Sondel-Cedarmas -- Following the benefits: Utilitarian attitudes towards the European Union: evidence from three Central and Eastern European countries / Marco Morini and Peter Plenta -- Part 5. Italy and Europe: From Consensus to Disenchantment. Between old-style nationalism and political realism: Italy's diplomatic resistance to the process of European integration between 1945 and 1957 / Gerardo Nicolosi -- Is the lira to blame? The European monetary "Snake" and the emergence of Italian anti- Europeanism / Lucrezia Ranieri -- Populism and Euroscepticism in Italy: outlining the historical roots of a long-standing interplay / Giovanni de Ghantuz Cubbe -- Populism, populists, European democracies and European Union: the Italian case / Marc Lazar.
Keywords: European Union; Populism -- Europe; Central-local government relations -- European Union countries; European federation; Europe -- Economic integration; European Union countries -- Economic conditions; Europe -- Politics and government -- 1989-; European Economic Community countries -- Economic conditions; POLITICAL SCIENCE / Political Ideologies / General; HISTORY / Europe / General